LANDSCAPE DESIGN ON THE SIDES OF THE BAGHDAD-BABEL ROAD "AN APPLIED MODEL FOR A REST AREA - & Jasim, Hussain (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The study was aimed to design the  landscape on the sides of Baghdad-Babel road and landscaping the aspects of this section of the road length of 1 km, which represents the main entrance of the province of Babel, which is the municipality of Alexandria to achieve the strategy of beautiful roads through the appropriate selection of types of vegetation and emphasis on local species and adapted to environment and soil, which is one of the main factors in the conservation of vegetation on the sides of the roads, as well as the preparation of a design proposal for a rest area on the right side of the section of the road under study to an area of ​​270,14.108 m2 is not intended for any future use, its currently used by drivers of heavy and medium vehicles and the regular vehicles and passengers while waiting at the entrance to the province of Babylon and provide an opportunity to reduce stress and fatigue on the driver and management of travel requirements and improve traffic safety by reducing traffic accident rates as a result of traffic density in this way.